Fabrication of PAN/PHCS adsorptive UF membranes with enhanced performance for dichlorophenol removal from water. Issue 19 (28th April 2014) - Gao, Yan; Qiao, Yuan; Yang, Sen
ABSTRACT A series of novel polyacrylonitrile (PAN) adsorptive UF membranes were prepared via the nonsolvent induced phase inversion method using adsorbent‐amphiphilic porous hollow carbonaceous microspheres (PHCSs) as additive. The resulted PAN/PHCS membranes were demonstrated to have better mechanical strength than the pure PAN membrane. The water fluxes of the PAN/PHCS membranes were slightly decrease; however, the rejections to pepsin were maintained at a high level (81–86%). The properties of the PAN/PHCS membranes for 2, 4‐dichlorophenol removal from water were investigated. The results showed that 2, 4‐dichlorophenol could be rapidly removed from water via adsorption mechanism by PAN/PHCS membranes, and the maximum reduction efficiency was up to 70%. The adsorption of 2, 4‐dichlorophenol to the membranes was reversible and the membranes could be regenerated facilely by water washing. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40837.